ANALISIS SPASIAL TIPOLOGI KERUSAKAN LAHAN BERBASIS SISTEM INFORMASI GEOGRAFIS (Spatial Analysis Of Land Damage Typology Based On Geographic Information System) - J Juhadi; Heri Tjahjono; Riza Arifudin (TATALOKA, 2014)
Analysis of spatial typology of land demage can give an idea on how community behavior was and can be used as an indicator of how society treats the land resources now and for the future. This paper aims to describe the spatial analysis of land demage typology based on geographic information system. The research was carried out in the hill-mountainous area of Kulonprogro, DIY. The approach was a mix of quantitative and qualitative research. The units of analysis are farm households and landform units. The study was conducted using survey and in-depth interviews. The results show that the typology of land demage rate is lower than the actual level typology of potential land demage, which means the level of potential land demage is not always directly proportional to the level of actual land demage. The factor of local wisdom in the study area plays an important role in the management of agricultural land.